Reviving the Legacy: Ancient Egyptian Civilization in Modern Arabic Poetry - Esat Ayyıldız (Darulfunun Ilahiyat)
This article examines the enduring influence of Ancient Egyptian civilization in contemporary Arabic poetry, focusing on the ways poets incorporate elements of Egypt’s ancient past into their literary works to preserve its memory for future generations. The subject, scope, and importance of this study lie in the exploration of the engagement with Ancient Egypt in various aspects, such as celebrating architectural marvels and acknowledging the wisdom and achievements of the civilization that once thrived along the Nile. The purpose of this research is to underscore the significance of the past in shaping present-day literary and cultural expressions, as well as the role of art in the construction of collective identity. The methodological framework involves a close analysis of selected poetic works, paying particular attention to the interplay between different cultural and historical influences, and demonstrating the vitality and adaptability of the Arab poetic tradition. In addition, this study highlights the implications of Ancient Egyptian civilization in contemporary Arabic poetry beyond the realm of literature, emphasizing the necessity of reevaluating the relationship between past and present and fostering a sense of continuity and connection with a shared history